Topic collections, 1938-1965. (Mass observation online. Update., 1937)
Material relating to Mass Observation surveys of gambling from 1939 to 1951, mostly from a 1947 survey commissioned by the National League for Education Against Gambling. This survey resulted in the production of File report 2560, 'Mass gambling', although the report was not published as had been originally intended (see David Dixon, 'From prohibition to regulation', 1991). Other material includes reports on greyhound racing in the early years of World War II, and surveys of Football Pools and feelings about a National Lottery in the immediate post-war years.